IMPLEMENTASI KONSEP BUILDING INFORMATION MODELLING (BIM) 5D PADA PEKERJAAN STRUKTUR UNTUK EFISIENSI BIAYA PROYEK - Pratama, Rizky Eka; Hendriyani, Irna; Pratiwi, Reno (Jurnal Teknologi Terpadu, 2024)
Technological advances have entered the 5.0 revolution, where technology in various fields, especially construction, is thriving. The technology is particularly useful in modeling, planning, cost and volume estimation, continuity, and building management. Almost all areas of work have now adopted automation with the use of software, including AEC (Architecture, Engineering and Construction). One of the technologies in the AEC field is Building Information Modelling (BIM), the BIM 5D Concept has proven to be efficient in handling cost control, as research shows that there is a minimal difference in computation in cost estimation. This study implemented BIM 5D on the Type 300 2-story boarding house construction project in Sepinggan Lestari Housing, Balikpapan. Based on the project's previous cost calculations, MS Excel and 2D images were then compared to Revit software. With a contract value of Rp. 3,275,204,419, the cost of concrete and ironing each is IDR. 156,929,007 and Rp. 550.910.751. Analysis shows that the use of BIM 5D results in more efficient volume and cost calculations than conventional methods. The volume calculation difference for ironing was 6.92%, and for concrete was 15.06%. The difference in ironing costs was 11.54%, and concrete was 15.06%, indicating that the consultant's calculated volume was greater than that of Revit. This study concluded that the implementation of BIM 5D could improve the accuracy of cost and efficiency calculations in construction projects.